2006
DOI: 10.1186/bcr1401
|View full text |Cite
|
Sign up to set email alerts
|

Key stages in mammary gland development - Involution: apoptosis and tissue remodelling that convert the mammary gland from milk factory to a quiescent organ

Abstract: Involution of the mammary gland is an essential process that removes the milk-producing epithelial cells when they become redundant at weaning. It is a two-step process that involves the death of the secretory epithelium and its replacement by adipocytes. During the first phase, remodelling is inhibited and apoptotic cells can be seen in the lumena of the alveoli. In the second phase, apoptosis is accompanied by remodelling of the surrounding stroma and re-differentiation of the adipocytes. Considerable effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
195
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(201 citation statements)
references
References 31 publications
(28 reference statements)
4
195
0
2
Order By: Relevance
“…At the end of lactation, when regular removal of milk ceases, the MG enters a tissue-remodeling process known as involution [22]. Early after weaning, the epithelial architecture is maintained by the recent exposure to elevated systemic hormones, e.g.…”
Section: Post-lactational Changes and Involutionmentioning
confidence: 99%
“…At the end of lactation, when regular removal of milk ceases, the MG enters a tissue-remodeling process known as involution [22]. Early after weaning, the epithelial architecture is maintained by the recent exposure to elevated systemic hormones, e.g.…”
Section: Post-lactational Changes and Involutionmentioning
confidence: 99%
“…Parturition induces full secretory differentiation and milk production. Upon weaning, the secretory cells are eliminated and the gland is remodeled to a duct system that resembles the mature nulliparous state (1). This process of mammary involution involves two sequential rounds of apoptosis.…”
mentioning
confidence: 99%
“…PMCA2 overexpression, on the other hand, may play a role in breast cancer progression by conferring resistance to apoptosis. intracellular calcium T he mammary gland undergoes a dramatic cycle of development and regression during reproduction (1). The virgin gland consists of a simple system of epithelial ducts.…”
mentioning
confidence: 99%
“…In addition, we previously reported that Nucling mediated apoptosis by suppressing the expression of the anti-apoptotic molecule galectin-3 via NF-B signaling (18). Apoptosis has been identified as a crucial part of involution in the mammary gland (13). However, it currently remains unknown whether Nucling controls apoptosis in mammary gland involution.…”
mentioning
confidence: 99%
“…Phagocytosis is a crucial contributor to the remodeling process and removal of cell debris and residual milk in the second phase of involution (12,13). Furthermore, a recent study demonstrated that mammary gland involution was characterized by the recruitment of macrophages with M2 characteristics, which is crucial for epithelial cell death and adipocyte repopulation (14).…”
mentioning
confidence: 99%